3D printed thermo-responsive electroconductive hydrogel and its application for motion sensor - Li, Yangyang; Zheng, Wenhui; Zhang, Jichi; Xu, Lijuan; Li, Bing; Dong, Jidong; Gao, Guo-Lin; Jiang, Zaixing (Frontiers in Materials, 2023)
Stimulus-responsive hydrogels with excellent conductivity have been widely used in electrical, electrochemical, biomedical, and other fields. It is still a challenge to prepare gels with high conductivity. In this paper, poly (N-isopropyl acrylamide) is 3D printed by changing the rheological properties of the printing solution with clay. By forming phytic acid cross-linked polyaniline conductive polymer network in situ on the poly (N-isopropyl acrylamide) matrix, 3D printing of thermally responsive conductive hybrid hydrogels was realized. The interpenetrating polymer network structure provides an electron transport path for hydrogels. The hydrogels have high porosity, strong interaction, high electrical conductivity, high thermal response sensitivity, and significant mechanical enhancement. The results show that the swelling and mechanical properties of the gel are influenced by soaking in different concentrations. The application scenario of the hydrogel was confirmed by a temperature-sensitive switch and finger motion detection.